2021
DOI: 10.3390/polym13183121
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Arnica montana Wastes after Extraction of the Ethanol Tincture: Application in Polymer-Based Matrices

Abstract: The waste solids remaining after the ethanolic extraction of arnica were proposed as raw material for the recovery of the remaining phenolic fraction. Greener processes based on intensification extraction, with microwave (MHG) and ultrasound (UAE) assistance and pressurized hot water extraction under subcritical conditions (AH), were studied. The entire process provided approximately 28% of phenolics for the sequence when MHG was used, 22% in the sequence where AH was employed, and the extracts showed up to 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Antioxidants derived from medicinal plants have been increasingly investigated for their various health benefits [ 67 ]. The antioxidant potential of arnica flower heads has been studied with the use of numerous chemical assays and their very high antioxidant activity has been demonstrated [ 19 , 42 , 68 ]. The present study confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants derived from medicinal plants have been increasingly investigated for their various health benefits [ 67 ]. The antioxidant potential of arnica flower heads has been studied with the use of numerous chemical assays and their very high antioxidant activity has been demonstrated [ 19 , 42 , 68 ]. The present study confirmed this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Žitek et al [ 24 ] reported apoptotic activity of A. montana flower head extracts against melanoma WM-266–4 cells. In turn, Flórez-Fernández et al [ 68 ] showed cytotoxic properties against colorectal cancer HCT-116 and pancreatic adenocarcinoma PSN1 cells. It was clearly shown in the present study that NF determined the quality of the studied extracts and, in consequence, their anticancer activity in the case of all the analyzed cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…can be determined via the propagule type during introduction [9], soil quality [7,9], soil and foliar fertilization [3,18], morphological features, and plant organs [23,24], and may be responsible for the biological activity of plant material [23][24][25][26][27]. There are reports available in the literature on the apoptotic activity of mountain arnica extracts against melanoma WM-266-4 cells [4] and cytotoxic properties against colorectal cancer HCT-116 cells [43]. The present study has shown that the stage of plant development, the solvent type, and their interactions can modify the chemical composition of extracts and their antitumor activity against human carcinoma (HeLa), colon (HT29), and colon metastatic SW620 cell lines.…”
Section: Anticancer Activitymentioning
confidence: 99%